Charteris-Black, Jonathan: Metaphors of coronavirus: Invisible enemy or zombie apocalypse? (Palgrave Macmillan, 2021. 317 pp. ISBN 978-3-030-85105-7 (paperback). E-book 978-3-030-85106-4) - Zhang, Yan (Onomázein, 2024)
-